ANDROID-BASED GARBAGE MANAGEMENT APPLICATION USING K-MEANS ALGORITHM ON RT 03/02 KEL. KARAWACI BARU - Abid, M. Nur Rois; Artanti, Sarah Camilla; Adiyati, Nita; Junaedi, Edi (Jurnal Teknik Informatika (Jutif), 2024)
Technological advances have brought significant changes in human life, one of which is the facilitation of access to information. Despite this, garbage management remains an important issue that requires serious attention. Without practical management efforts, the negative environmental impact will continue to increase. Therefore, the study aims to develop an Android-based waste management application using the Waterfall methodology approach and the K-means algorithm method to allow users to group the type of garbage according to its characteristics so that the waste management process can be done more systematically and efficiently. From the application design and testing results, it was concluded that this waste management application can serve as an effective tool in helping people manage their garbage more efficiently. With this digital platform, it is expected that public awareness of the importance of garbage management can be increased and contribute to the maintenance of hygiene and the health of the environment. Thus, the Android-based waste management application has great potential to be a relevant solution in dealing with the problem of waste management. With this digital approach, it is expected that people can be more effective in regulating and utilizing garbage and actively participate in efforts to maintain environmental sustainability for generations to come.